Getting into hot water: Water quality in tropical lakes in relation to their utilisation. Issue 1 (June 2021) - May, L; Aura, C Mulanda; Becker, V; Briddon, C L; Carvalho, L R; Dobel, A J; Jamwal, P; Kamphuis, B; Marinho, M M; McGowan, S; Nandini, S; Nyamweya, C; et al.
Abstract: Over-exploitation of tropical lakes and reservoirs ('lakes') causes water quality problems that occur as a result of competing socio-economic demands and the presence of feedback loops within the system that exacerbate the situation. We review well documented case studies from Brazil, India, Indonesia, Kenya, Malaysia and Mexico to examine the effect that changes in water quality and quantity have had on the utilisation of these tropical lakes. By comparing the different approaches used to improve their sustainable management, we have found that nutrient enrichment is one of the most important and widespread water quality problems, causing adverse effects such as algal blooms, nuisance levels of aquatic plants, low oxygen levels and elevated greenhouse gas emissions. These effects restrict the use of these lakes for water supply, fisheries, recreation, tourism and wildlife. We conclude that tropical lakes require better management, urgently, to restore the ecosystem services that they deliver to man and nature. However, to be effective, the development of sustainable management programmes needs to be underpinned by reliable scientific evidence and the results of extensive stakeholder engagement activities. We note that, currently, there is little information available on how tropical lakes respond to management interventions that can be used to guide these activities. Further research is needed to address this knowledge gap.